Tinnitus in Normal-Hearing Participants after Exposure to Intense Low-Frequency Sound and in Ménière’s Disease Patients - Ueberfuhr, Margarete Anna; Wiegrebe, Lutz; Krause, Eike; Gürkov, Robert; Drexl, Markus (Frontiers in Neurology, 2017)
Tinnitus is one of the three classical symptoms of Ménière's Disease (MD), an inner ear disease which is often accompanied by endolymphatic hydrops. Previous studies indicate that tinnitus in MD patients is dominated by low frequencies, whereas tinnitus in non-hydropic pathologies is typically higher in frequency. Tinnitus of rather low-frequency quality was also reported to occur for about 90 s in normal-hearing participants after presentation of intense, low-frequency (LF) sound (120 dB SPL, 30 Hz, 90 s). LF sound has been demonstrated to also cause temporary endolymphatic hydrops in animal models. Here, we quantify tinnitus in two study groups with chronic (MD patients) and presumably transient endolymphatic hydrops (normal-hearing participants after LF-exposure) with a psychophysical procedure. Participants matched their tinnitus either with a pure tone of adjustable frequency and level or with a noise of adjustable spectral shape and level. Sensation levels of matching stimuli were lower for MD patients (mean: 8 dB SL) than for normal-hearing participants (mean: 15 dB SL).Transient tinnitus after LF-exposure occurred in all normal-hearing participants (N=28). About half of the normal-hearing participants matched noise to their tinnitus, the other half a pure tone with frequencies below 2 kHz. MD patients matched their tinnitus with either high-frequency pure tones, mainly above 3 kHz, or with a noise. Despite a significant proportion of MD patients matching low-pass (roaring) noises to their tinnitus, the range of matched stimuli was more heterogeneous than previous data suggested. We propose that in those participants with noise-like tinnitus, the percept is probably generated by increased spontaneous activity of auditory nerve fibers with a broad range of characteristic frequencies, due to an impaired ion balance in the cochlea. For tonal tinnitus additional mechanisms are conceivable: Focal hair cell loss can result in decreased auditory nerve firing and a central auditory overcompensation. Also, normal-hearing participants after LF-exposure experience alterations in spontaneous otoacoustic emissions, which may contribute to a transient tonal tinnitus.